Impact of Sleep Deprivation on the Hypothalamic–Pituitary–Gonadal Axis and Erectile Tissue - Lee, Dong Sup; Choi, Jin Bong; Sohn, Dong Wan (Journal of sexual medicine, 2019)
It is unclear how sleep deprivation (SD) exerts a negative effect on men’s health in terms of hypogonadism. To evaluate the hypothalamic–pituitary–gonadal (HPG) axis in subjects with SD and ultimately to evaluate the erectile tissue in response to the hormonal changes. 56 male Wistar rats were used. First, 16 rats (16 weeks old) were subjected to 72 hours of SD, and the following were compared with 16 control rats: (i) levels of gonadotropin-releasing hormone (GnRH), luteinizing hormone (LH), follicle-stimulating hormone (FSH), testosterone (T), and cortisol; (ii) the expression of the kisspeptin mRNA in the brain; and (iii) assessment of immunohistochemistry (IHC) of brain and testis. To further investigate whether testosterone reduction due to SD could affect erectile tissue, an additional 24 rats were divided into 3 groups (control, SD, and SD with T supplementation [SDT]) and compared: (i) T and cortisol levels were quantified, and (ii) endothelial nitric oxide synthase (eNOS)/ neuronal nitric oxide synthase (nNOS)/NOX-2 expression in cavernosal tissue was assessed by measuring mRNA levels and performing Western blotting and IHC. Compared with the levels in the control group, the LH level was markedly decreased, and T levels were subsequently decreased in the SD group, whereas the level of the kisspeptin mRNA and IHC for kisspeptin, GnRH, and FSH were not different. In cavernosal tissues, levels of the eNOS/nNOS mRNAs and proteins tended to be lower, and NOX-2 levels (mRNA and protein) tended to be higher in the SD group than those in the control group and SDT group. IHC for eNOS/nNOS revealed lower-intensity staining in the SD group than in the control and SDT groups, whereas the NOX-2 intensity was higher in the SD group than in the other groups. A lower cortisol level was observed in the control group than in the SD and SDT groups, whereas the level was similar between the SD and SDT groups. The intracavernosal pressure/mean arterial blood pressure (%) values were also decreased in the SD group but not on testosterone injection. Even short-term SD can produce secondary hypogonadism, which impairs men’s health. To the best of our knowledge, this study is the first to show the effects of SD on the whole HPG axis. The weakness is that this study only investigated acute SD. Based on the findings from this study, acute SD causes pituitary hypogonadism, and reduced T levels decrease erectile function by inducing superoxide accumulation in the cavernosal tissue and inhibiting nitric oxide synthase activity. Lee DS, Choi JB, Sohn DW. Impact of Sleep Deprivation on the Hypothalamic–Pituitary–Gonadal Axis and Erectile Tissue. J Sex Med 2019;16:5–16.